Relevance of split In vitro fertilization-intracytoplasmic sperm injection method of insemination in normozoospermic and mildly oligospermic men: A retrospective study - Geeta Goswami; M Devi Gouri (Wolters Kluwer Medknow Publications, 2020)
Background: Use of intracytoplasmic sperm injection (ICSI) is generally considered redundant in cases of normozoospermia, or mild male factor cases of infertility and conventional method of insemination is advocated. However, there is a risk of low fertilization or total fertilization failure (TFF) and to avoid this, split in vitro fertilization (IVF)-ICSI method of insemination is advised. In our study, we have shown that not only TFF is avoided with split method of insemination, but also cancellation of embryo transfer (ET) can be avoided in a significant number of IVF cycles. Aims: This study aimed to assess whether the IVF-ICSI split insemination method was able to reduce the risk of ET cancellation in couples with normal or mild sperm characteristics. Settings and Design: It is a retrospective study including a total of 107 split insemination cycles done at our center. Materials and Methods: The female partner's age was under 37 years, and at least ten oocytes were retrieved in all cycles. Sibling oocytes were randomly allocated to IVF or ICSI. Statistical analysis was carried out using Graphpad Prism, Instat. Results and Conclusion: The fertilization rate in oocytes kept in conventional IVF was significantly higher (79.8%) compared to that of oocytes injected through ICSI (69.1%). Only one couple had TFF. In majority of the cycles, i.e., 97 out of 107 cycles, the mode of insemination did not affect the fertilization rate or embryo quality. Nearly 28% of the cycles were saved from ET cancellation by adopting the split insemination method. "Split IVF-ICSI" approach can save a significant number of ART cycles and is found to be cost-effective as it avoids incurring the cost of two ART cycles.